2012
DOI: 10.1108/02686901211217996
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee effectiveness and timeliness of reporting: Indonesian evidence

Abstract: Purpose -The purpose of this paper is to examine the association between audit committee effectiveness and timeliness of reporting. Specifically, the paper investigates whether there is any relationship between effectiveness of an audit committee and submission of audited financial statements to the Indonesian Stock Exchange (IDX). Design/methodology/approach -Audit committee effectiveness is measured by an index based on the framework developed by DeZoort et al. Timeliness of reporting is defined as the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 50 publications
1
50
0
12
Order By: Relevance
“…It can be based on the total assets value, total sales, market capitalization, number of workers, and so on (Niresh and Velnampy, 2014). The greater the assets of a company, the greater is the invested capital, the greater the total sales of a company, the more money will be turned-over and the larger the market capitalization and the greater the company will be known by the public (Ika and Ghazali, 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It can be based on the total assets value, total sales, market capitalization, number of workers, and so on (Niresh and Velnampy, 2014). The greater the assets of a company, the greater is the invested capital, the greater the total sales of a company, the more money will be turned-over and the larger the market capitalization and the greater the company will be known by the public (Ika and Ghazali, 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Previous studies reported that the effectiveness of audit committees is to some extent dependent on the characteristics of the committee, such as its size (Dellaportas et al 2012;Herdjiono and Sari 2017). To be effective in controlling and monitoring managers' behaviour, the audit committee must have enough members to carry out its responsibilities (Vicknair et al 1993), with sufficient resources (Kalbers and Fogarty 1993).…”
Section: Audit Committee Sizementioning
confidence: 99%
“…Based on the premises of the agency theory, the conflict between managers and shareholders often motivates managers to act in their own best interest and against those of shareholders, especially when opportunistic behaviour is involved in the process (Jensen and Meckling 1976;Dellaportas et al 2012). Therefore, in an environment without monitoring tools and effective market regulations, managers are more likely to deviate from protecting the shareholders' interests (Turley and Zaman 2004;Al-Matari et al 2012).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably, IFRS' stresses fair value accounting as required by most IFRS standards (Ahmed, Chalmers, & Khlif, 2013). The adoption is expected to lower the audit delay and provide a readable financial statement to stakeholders within the time span regulated (Oussii & Boulila Taktak, 2018), this is because financial reporting timeliness has for long been acknowledged as one of the distinct feature of financial reporting (Sultana, Singh, der Zhan & Mitchell, 2015, Ika & Ghazali, 2012Abbott, Parker & Peters, 2012).…”
Section: Introductionmentioning
confidence: 99%